1975
DOI: 10.1001/archneur.1975.00490530049003
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Head Trauma Syndromes and Their Relationship to Migraine

Abstract: The clinical spectrum of juvenile head trauma syndromes was derived from an analysis of 50 attacks in 25 patients. Attacks were grouped into four clinical types: (1) hemiparesis; (2) somnolence, irritability, and vomiting; (3) blindness; and (4) brain stem signs. Our evidence shows that these four types are different manifestations of a common underlying process. All attacks followed mild head trauma after a latent interval, generally of one to ten minutes. Forty of the 50 attacks occurred in patients under 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 15 publications
2
32
0
1
Order By: Relevance
“…Also, in 1975 Haas [7] suggested that the same pathogenic mechanism existed in PTH and migraine in young patients, however, that the trauma was only a triggering momentum. In 1993, the same author did not find any relation between the severity of a trauma and the onset of chronic headache, and confirmed this in 1997 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in 1975 Haas [7] suggested that the same pathogenic mechanism existed in PTH and migraine in young patients, however, that the trauma was only a triggering momentum. In 1993, the same author did not find any relation between the severity of a trauma and the onset of chronic headache, and confirmed this in 1997 [8].…”
Section: Introductionmentioning
confidence: 99%
“…in previously reported cases of JHTS in which the delay between head injury and the onset of the neurological episodes varied from several seconds, minutes, and hours up to 2 days, 7,8,25,27,29) and the episodes lasted from several minutes to several days. Presumably, the majority of the acute type of JHTS, especially those at intervals of several seconds or minutes, involve electrical and/or neuronal reflex phenomena such as cortical spreading depression 25,29) or a trigeminovascular response, because these phenomena appear immediately after the input of stimuli.…”
Section: Discussionmentioning
confidence: 83%
“…8) Cerebral angiography found no abnormalities in six of 37 patients with JHTS. 25) In contrast, investigation of migraine suggested that vasodilation and hyperemia are the underlying causes of JHTS, but there was no radiological evidence.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations